THE MIDDLE CLASS, THE YOUTH, THE HIGHWAYS: PRODUCTION OF SPACE AND URBAN MEMORY IN BLOK M, JAKARTA - Novantara, Bimana; Bachrioktora, Yudi; Kurnia, Lilawati (UI Scholars Hub, 2025)
This paper examines the historical and contemporary dynamics of the Blok M area in Jakarta as a public space undergoing a process of spatial, cultural, and symbolic transformation. Using Henri Lefebvre’s theory of the production of space and then relating it to the discourse of urban memory according to Abidin Kusno, this study traces how Blok M developed from the modernist urban planning of Kebayoran Baru after independence to be the epicenter of youth festivity, then declined until it rose again through a place that utilized the memory of this area in the past. This study highlights how the politics of marginalization, cultural practices, and power discourses through infrastructure shape the meaning of an urban area in Jakarta. By analyzing historical narratives, visual artefacts, and urban planning policies, this article argues that changes in Blok M represent physical transformation and struggle over collective memory, middle-class identity, and power relations in the production of the contemporary urban space of Jakarta.